PENURUNAN LOGAM Hg DALAM AIR MENGGUNAKAN SISTEM SUB-SURFACE FLOW CONSTRUCTED WETLAND (SSF-CW) : STUDI STABILITAS SISTEM - Rikhanatul Firdausy Puspitasari; Agus Prasetya; Edia Rahayuningsih (PROSIDING SNAST, 2018)
High rates of mercury contamination were found in traditional gold mining areas. This problem might occur due to the use of amalgamation process in gold extraction process done in traditional gold mining areas by dissolving the gold-bearing rocks with mercury (Hg). The use of mercury in the gold mining activity has contaminated the water with Hg which might lead to serious health problems. This research was done by discharging the wastewater contaminated by Hg to enter a system called the Sub-Surface Flow Constructed Wetland (SSF-SW). The system employed a mixture of soil and the fibers of water hyacinth as the media which media was also planted with Echinodorus palaefolius L. The research was done by flowing the wastewater containing HgCl2 at 8.59 mg/L. The experiments applied flow rate at 6.3 L/hour and pH between 6-7 in room temperature. Samples were collected at hour 0; 3.5; 7; 10.5 every day. The SSF-CW system was continually run for 10.5 hours and 13.5 hour batch. The result of this research showed the efficiency of Hg removal reached 92.798%. The percentages of Hg accumulation in Echinodorus palaefolius L. were found at 65.96% in the roots, 18.75% in the stems, and 15.29% in the leaves. This research found that the SSF-CW offers a stable system to reduce the mercury levels as shown in the growth of the plant and the total Hg removal efficiency. Plants with Hg exposure have distinct patterns of chlorosis. Some leaves turning yellow and die, others start with new growth. In addition, the growth of Echinodorus palaefolius L. was also influenced by the amount of nutrients in the soil. The rate of metal transfer from the roots to the buds of mexican sword plants was found at 0.236. This research found that the SSF-CW offers a stable system to reduce the mercury levels as shown in the growth of the plant and the total Hg removal efficiency. Plants with Hg exposure have distinct patterns of chlorosis. Some leaves turning yellow and die, others start with new growth. In addition, the growth of Echinodorus palaefolius L. was also influenced by the amount of nutrients in the soil.